New or rare Madagascar tiger beetles—25. Pogonostoma (Microstenocera) borisbubeniki sp. nov., compared to P. (M.) andreevae Moravec, 2007 and a revised key to the species-group (Coleoptera: Cicindelidae) - Moravec, Jiří; Trýzna, Miloš (Zootaxa, 2022)
Pogonostoma (Microstenocera) borisbubeniki sp. nov., is described from the Ambohitantely Special Reserve on the north-eastern edge of the Central Highlands, Madagascar. The new species is compared to the externally similar P. (Microstenocera) andreevae Moravec, 2007, and both are treated as members of the P. (Microstenocera) fleutiauxi species-group (as proposed in the monograph of the genus Pogonostoma Klug, 1835 by Moravec 2007). A revised key to species of the species-group is presented to supplement the key in the monograph. Habitus and diagnostic characters of the new species are illustrated in colour photographs. Not-yet-published photographs of a male allotype of P. (M.) andreevae and important diagnostic characters of this similar species, including those of one newly caught female, are provided to complete the illustrations published previously in the monograph. The habitat and ecology of the new species with essential maps of disjunct distributions of the two species are also presented.